Hokkien in Penang : Struggles of a Minor Language - Wolter, Lynsey K.; Lim, Carmen (My University, 2017)
The purpose of this study was to preserve and possibly revitalize Penang Hokkien in the future by introducing a writing system that works well for the community, as well as raising awareness about the values of minor languages.
Color poster with text, tables, and images.
Keywords: Penang, Malaysia; Language revitalization; Linguistics; Malaysia; Penang Hokkien; Posters